Burying heads in Geneva sands: Without dismantling the sectarian crux of Assad's rule, Syria peace talks are unlikely to usher in stability - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2015)
A web of corruption involving the Assad family, the security apparatus, and their business cohorts has been a major factor behind the outbreak of the Syrian revolt that started in 2011. UN-facilitated talks between the regime and the opposition are set to convene in Geneva in January 2016, after the refugee crisis in Europe and Russia's entry into the Syrian war prompted a renewed international push to solve the conflict in Vienna. The proposed "thematic" negotiations ambitiously cover humanitarian issues; the military, terrorism, and security; the constitution and political systems; institutions and reconstruction. Germany set up an international fund for the rebuilding of Syria in 2013. But a deal that does not tackle fundamental imbalances linked to the domination of Assad's Alawite sect risks repeating the reconstruction debacle of post-Saddam Iraq, inviting the Sunni majority to scuttle any stabilization and recovery efforts. ( SWP Comments)
Keywords: 320